Nicole and the tower blocks - Christophe Meunier (Strenae)
Andrée Clair and Bernadette Després’ “Nicole” series is unique in the history of children’s picture books in France. Published between 1969 and 1978 by the communist publisher La Farandole, it is the only series for children which provides a positive image of large-scale council estates [grands ensembles]. This article sets the series in its context of the French publishing landscape of the 1970’s, and makes the connection between this series and the “triumph of modernism” discourse in the media and in state policy on modern urban council estates in the postwar period. In so doing, it analyses the novelty of the iconotextual narrative of the “Nicole” series, and sheds light on the ideological position-taking of both author and artist.